Distinctive features and prognostic utility of neutrophil in severe patients with Klebsiella pneumoniae infection - Du, Chunjing; Lu, Ming; Zheng, Jiajia; Liu, Chao; Yang, Ping; Yi, Juan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundNeutrophil plays a pivotal role in the management of Klebsiella pneumoniae infection. Delineate the clinical characteristics and prognostic utility of neutrophil in severe patients with K. pneumoniae infection are crucial for clinical management and prognostic assessment.MethodsK. pneumoniae patients with different infection sites were enrolled from Medical Information Mart for Intensive Care IV and eICU Collaborative Research Database. Temporal variations of neutrophil counts within 30 days of clinical onset were examined using locally weighted scatterplot smoothing curves. Logistic regression analysis was performed to assess the relationship between neutrophil counts and hospital mortality.ResultsA total of 1,705 patients caused by K. pneumonia were included in the study. The non-survivor group exhibited a comparatively older age and a higher proportion of K. pneumoniae infections originating from respiratory and bloodstream sources compared to the survivor group (38.4% vs 21.1%, p<0.0001, and 15.1% vs 10.3%, p=0.021). Patients combined with multiple drug resistance strains, respiratory infection, liver disease, and above 60 years exhibited a specific dynamic process of neutrophil levels. Neutrophils counts peaked at admission and 1-2 weeks later. There was a ‘U’-shaped relationship between neutrophil counts and hospital mortality.ConclusionsNeutrophils in K. pneumoniae infected patients have distinctive features and dynamic clinical trajectories. Close monitoring of severe patients infected with K. pneumoniae upon admission and during the first 1-2 weeks after admission is of utmost importance, particularly for patients with a neutrophil count exceeding 8.0×109/L.